Estrategias Metodológicas Cognitivas En El Desarrollo De La Destreza Auditiva En El Aprendizaje Del Idioma Inglés - López, Edison Renato Ruiz; Amaguaya, Patricia Pilar Moyota; Yerovi, Enrique Jesús Guambo (European Scientific Journal, ESJ, 2018)
This paper focuses on examining the application of cognitive methodological strategies and the effective development of listening skill in the English teaching process of the fourth level students room D and E of the Language Center of the National University of Chimborazo. This research had a quasi-experimental design. It is bibliographical, and it has a field and social intervention. The level of research is explanatory, descriptive, and correlational. The population under study comprised of 63 university students whom were divided into control and experimental groups. Taking into account the fact that there is an imbalance in the training of the English language skills within the execution of the educational process, it was made as a theoretical basis for the research. Later, a test and a post-test were applied to the two groups of students. Here, the application of cognitive methodological strategies was experimented in order to verify the relationship between the two variables. It was concluded that the mentioned strategies promote the development of the listening skill, considered by the writers as fundamental in the teaching of the languages.